FORMULASI DAN SITOTOKSISITAS NANOPARTIKEL PEKTIN PENAUT SILANG KITOSAN RANTAI SEDANG TERINTEGRASI RIBOSOME-INACTIVATING PROTEIN Mirabilis jalapa L. (PROTEIN MJ) DENGAN PENANDA ANTI EPCAM - , ANGGUN FERANISA, Prof. Dr. Sismindari, SU., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In Indonesia, breast cancer cases are 19.2% and its death cases are 25.5%. Usually, cancer treatment used cytotoxic effect of compounds. Cytotoxic effect of Ribosome-Inactivating Proteins (RIPs) on malignant cells are higher than normal cells. RIPs need delivery system to protect it from proteosome degradation in endosome. Chitosan nanoparticles have âproton sponge hypothesisâ mechanism to protect proteins from degradation. Chitosan and pectin is used as basic formula of drug delivery because of its biodegradable and biocompatible properties. Chitosan-pectin nanoparticles can be formulated by polyelectrolit complex. EpCAM showed excessive expression in breast cancer cells thus can be used as a therapeutic biomarker. Thus, the aim of this research was to develop chitosanpectin nanoparticles integrated by RIPs and conjugated with anti EpCAM for breast cancer therapy. Protein was extracted from M.jalapa leaves (MJ protein). RIPs activity was assayed by cutting pDNA. MJ protein were loaded into chitosan nanoparticles using medium viscous chitosan and pectin as cross-linker with polyelectrolit complex method. Anti EpCAM was conjugated to MJ protein chitosan-pectin nanoparticles by carbodiimide reaction and characterized for its entrapment efficiency, morphology by transmission electron microscope, particles size, and zeta potential. MJ protein nanoparticles conjugated anti EpCAM and without anti Ep-CAM were cytotoxicity assayed toward T47D and Vero cell lines. MJ protein was able to cleave the pDNA into linear and nicked-circular ones. The nanoparticles optimal concentration of medium viscous chitosan: MJ protein : pectin was 0.01%: 0.01%: 1% (m/v). A high entrapment efficiency of MJ protein nanoparticles was 98.97 Â± 0.07%. Morphology nanoparticles showed an amorphic structure with 200.00nm particles size. The nanoparticles conjugated anti EpCAM showed average particles size 367.67nm, polydispersity index 0.332, and zeta potential +39.97mV. MJ protein chitosan-pectin nanoparticles with anti EpCAM conjugated and without anti EpCAM both effectively increased cytotoxicity effects toward T47D and Vero cell lines than MJ proteins without nanoparticles.